Effects of physical activity on pain, fatigue, inflammation and cardiovascular risk in rheumatoid arthritis - Małgorzata Wirkijowska; Jakub Wirkijowski; Paulina Woźniak; Wiktoria Gajek-Flanczewska; Sebastian Flanczewski; Ewa Wietrzykowska; Martyna Śliwińska; Katarzyna Wójtowicz; Agata Walczak; Dominika Sobolewska; Anna Podraza; Katarzyna Michalczyk-Fraszka (Quality in Sport)
Introduction and aim of the study: The prevalence of rheumatoid arthritis in our society is relatively high. As a result, the number of people requiring some kind of treatment or improvement in quality of life is also increasing day by day. In our study, we aimed to explore the topic of reducing discomfort associated with this condition. We decided to examine the effects of physical activity on individual complaints and systemic symptoms. We summarised the influence of different exercises on pain, fatigue, inflammation, and the cardiovascular system.